e-learning Platforms in Higher Education: An Analysis of Institutional Planning, Implementation and Evaluation Strategies - Attah Emmanuel (International Journal of Education Sciences, 2025)
This quantitative study investigates the impact of e-learning platforms on student learning outcomes in higher education, focusing on institutional planning, implementation, and evaluation strategies. A descriptive-correlational research design was employed, surveying 100 administrators, faculty, and students from various higher education institutions. The results show significant positive correlations between platform organization, user-friendliness, instructor feedback, technical support, and student motivation. Well-structured platforms with clear communication of learning objectives, quality technical support, and regular instructor feedback foster a conducive learning environment, improving academic performance and engagement. Students were better able to comprehend course expectations thanks to well-structured platforms that clearly communicated learning objectives, which promoted goal-oriented learning. Furthermore, platforms that provided smooth technical assistance made sure that students' access and participation were not severely disrupted. Students' confidence was further bolstered by regular instructor feedback, which encouraged active engagement and a deeper understanding of the course materials. These results are consistent with previous research, which highlights how important well-considered platform design and strong support networks are to attaining good learning outcomes. The findings align with existing literature, emphasizing the critical role of thoughtful platform design in achieving successful learning outcomes. Recommendations for enhancing platform effectiveness include improving organization and clarity, investing in user-centered design and technical support, promoting regular instructor feedback, fostering student motivation, and continuously evaluating platform effectiveness.
Keywords: E-learning platforms; evaluation strategies; higher education; implementation; institutional planning; student learning outcomes